Салтово-маяцький кремаційний могильник біля с. Нижній Бишкин на Сіверському Дінці - Голубєв, А.М. (Археологія, 2017)
До наукового обігу вводиться новий салтово-маяцький могильник за обрядом тілоспалення та матеріали з двох поховань, що виявлені на ньому. Presented to the scientific circlesis an information on a new large Saltiv-Maiaky burial ground with cremations near Nyzhnii Byshkyn Village in the Donets River upper region and on two burials discovered there. The materials from the assemblages recorded have their wide analogies in Saltiv culture assemblages of the Donets River region and beyond. Floral ornament and zoomorphic depictions on belt sets allow the author to refer the burials to the final stage of Saltiv culture existence in the region. В научный оборот вводится информация о новом, большом, салтово-маяцком кремационном могильнике возле с. Нижний Бишкин в Верхнем Подонцовье и двух погребениях выявленных на нем. Материалы из зафиксированных комплексов имеют широкие аналогии в салтовских комплексах Подонцовья и за его пределами. Растительный орнамент и зооморфные изображения элементов ременной гарнитуры дают основания относить погребения к финальному этапу существования салтовской культуры в регионе.